Impact of exchange rate fluctuation on Square Pharmaceuticals PLC’s financial performance - Sreaya, Iffat Sobha (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.